The Influence of Gold, Rhodium, and Flexy Blue Titanium Esthetic Surface Coating of NiTi Archwire on Mutans Streptococci Adhesion: An in Vitro Study - Haider Qasim Khazaal; Shaymaa Shaker Taha (Frontiers in Biomedical Technologies)
Purpose: Orthodontic archwires play an important part in the enamel demineralization during orthodontic treatment. Dental caries is thought to be caused by the adhesion and colonization of mutans streptococci on these surfaces, followed by the formation of pathogenic plaque. This research was conducted with the purpose of testing and comparing the adhesion of mutans streptococci to a variety of aesthetic archwires as well as a conventional archwire made of NiTi.